Comparison of match performance indicators of successful and unsuccessful teams in Turkish Super League - Gökhan Atasever; Kemalettin Seren; Hasan Hüseyin Yılmaz (ROL Spor Bilimleri Dergisi)
The aim of this study is to compare the match performance indicators of the successful and unsuccessful teams in the Turkish Super League in the 2018-2019 season. In the study group of the research, those who finished the super league in the top 3 and participated in the Champions league and UEFA European league; Bursaspor, which fell to a lower league by finishing in the last 3 places with Galatasaray, Medipol Başakşehir and Beşiktaş, formed the teams of Metropolitan Municipality Erzurumspor and Akhisarspor. Match performance variables; total running distance, high-speed running distance, high-speed running distance while having the ball, high-speed running distance when the ball is in the opponent's position, time to win the ball and team length. SPSS 25 package program was used for the analysis of the obtained data and independent sample t-test was used for pairwise comparison of the data. In all evaluations, the level of significance was taken as p<0.05. There was a statistically significant difference between the successful and unsuccessful teams in favor of the unsuccessful teams in the total running distance parameter, the high-speed running distance while having the ball, the high-speed running distance when the ball was in the opponent's possession, and the successful teams in the recovery time in favor of the team length and high-speed running distance parameters. It was determined that there was no statistically significant difference. As a result; It was found that there is a high correlation between the results of our study and the league rankings of the teams in the study group at the end of the season.